Reply to 'Lifshitz-point critical behaviour to O(εL 2)' - Albuquerque, Luiz C. de [UNESP]; Leite, Marcelo M. (Iop Publishing Ltd, 2002)
We reply to recent comment by Diehl and Shpot (2001J. Phys.A: Math. Gen. 34 9101) criticizing our paper (Albuquerque L C and Leite M M 2001J. Phys. A: Math. Gen. 34 L327). We show that the approximation we use for evaluating higher loop integrals is consistent with homogeneity. A new renormalization group approach is presented in order to compare the two methods with high-precision numerical data concerning the uniaxial case. We stress that isotropic behaviour cannot be obtained from anisotropic behaviour.